Saving Trends in Southeast Asia : A Cross-Country Analysis - Faruqee, Hamid; Husain, Aasim (Washington, D.C. : International Monetary Fund, 1995)
This paper investigates the long-run pattern of private saving in Indonesia, Malaysia, Singapore, and Thailand. These countries have not only maintained saving levels that are currently among the highest in the world but have also experienced a sustained increase in their rate of private saving over the past twenty years. Using a cointegration approach, this paper empirically examines the economic determinants underlying the saving trends in this group and the extent to which these countries share a common experience with respect to the factors accounting for their strong saving performance. The findings suggest that demographic shifts have been an important factor underlying regional saving trends with a similar long-run impact in each country, except for Indonesia where the effects of demographics have been even more pronounced.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet